Assessment of user's satisfaction with neighbourhood facilities in public housing estates in Akure, Nigeria. Issue 5 (17th January 2020) - Fakere, Alexander Adeyemi; Duke-Henshaw, Oluwadunsin Faith
Abstract : Purpose: This study aims at evaluating the state of neighbourhood facilities and how this influences the well-being of the residents taking into consideration their perception and satisfaction with the facilities. This is because availability and accessibility of neighbourhood facilities in housing estates play important roles in the quality of life of the residents. Design/methodology/approach: The paper adopts a cross-sectional survey of 301 housing units using structured questionnaire and direct observations in three public housing estates in Akure, namely, Ijapo, Alagbaka and Oba-Ile Housing Estates. Data obtained were analysed using descriptive analysis, mean scoring and categorical regression analysis to examine the effects of adequacy, accessibility and physical condition of the neighbourhood facilities on user's satisfaction. Findings: The findings showed that religious centres had the highest rating in all aspects of the study in the study estates, whereas fire service station was rated the least. Most of the independent variables significantly explained satisfaction except for accessibility to schools. The model explained 98.2 per cent of the variance in the level of satisfaction with Multiple R 2 of 0.982 and p = 0.000. Practical implications: The findings imply that there should be proper planning and regular maintenance of neighbourhood facilities within the housing estates in Akure to enhance user's satisfaction with such facilities. Originality/value: The study highlights the benefits of having neighbourhood facilities that are adequate, accessible and in good condition to enhance user's satisfaction.